Reader Response: Use of Whole-Genome Sequencing for Mitochondrial Disease Diagnosis. (3rd January 2023) - Schon, Katherine; Chinnery, Patrick
Abstract : We were interested to read this study, in which the authors applied a "genomics first" approach in 242 adult patients. 1 They identified 3 patients from 2 families with an adult-onset peroxisomal disorder, alpha-methylacyl-CoA racemase deficiency. This condition was identified in 3 families with suspected mitochondrial disorders in the 100, 000 Genomes Project and 1 patient in the whole-exome sequencing study by Theunissen et al. 2, 3